Prospective cost analysis of early video capsule endoscopy versus standard of care in non-hematemesis gastrointestinal bleeding: a non-inferiority study. (2nd January 2020) - Jawaid, Salmaan; Marya, Neil B.; Hicks, Michelle; Marshall, Christopher; Bhattacharya, Kanishka; Cave, David
Abstract: Background and aim: A non-inferiority cost analysis was performed to assess if the early capsule approach would incur higher costs than the standard of care approach in patients presenting with non-hematemesis gastrointestinal bleeding. Methods: A prospective non-inferiority cost analysis was performed on patients receiving either an early video capsule as the first diagnostic procedure or an endoscopic procedure as determined by gastroenterology staff that were not involved in the study. Primary outcome was total direct costs incurred in both groups. Results: Forty-five patients and 42 patients were enrolled into the early capsule and standard of care arms, respectively. There was no difference in total direct cost per inpatient case in both groups (7, 362 vs 7, 148, p = 0.77 [CI = −2, 285–2, 315, equivalent margin = –3, 100]). Localization of a bleeding source after the first diagnostic procedure was identified more frequently in the early capsule group (69.2% vs 27.9%, p = 0.0003). If patients were discharged after their last non-diagnostic evaluation, then length of stay could be decreased by 50% in both groups (58.5 to 31.6 h, p = 0.02 in the early capsule group and 69.4 to 39.2 h in the standard of care group p = 0.001). Projections indicate the fastest a patient with non-diagnostic evaluations could be discharged is 0.88 days in the early capsule group vs 1.63 days in the standard of care group ( p = 0.0005). Discussion: In patients with non-hematemesis bleeding, video capsule endoscopy may be a more efficient diagnostic approach than the standard of care approach, since it detects bleeding significantly more often without an increase in healthcare costs.